2019
DOI: 10.1177/1045389x19879998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selectively triggered photothermal particles on shape memory polymer composites: An investigation on structural performance, thermomechanical characteristics and photothermal behaviour

Abstract: Light-activated shape memory polymer composites (LASMPCs) have the ability to facilitate breakthrough technological advancements in aerospace and space engineering applications since the shape memory effect can be remotely controlled by a light beam. Introduction of rare-earth organic complexes–based photothermal fillers such as Nd(TTA)3Phen and Yb(TTA)3Phen into thermally activated shape memory polymers has been reported as a convenient and commercially available approach to prepare light-activated shape memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Carbon fiber LASMPC materials are capable of near-infrared light with a maximal power density of 2W/cm 2 for actuation, and these carbon-based filler materials had demonstrated developed not only photothermal efficiency but also enhanced structural properties . The effects of rare earth organic compounds and glass fiber filler on the main matrix have been tested by Herath et al, and the various properties have been investigated. It has been found that the photothermal triggering capacity of the SMPC increased drastically with different weight percentages.…”
Section: Actuation Mechanism For Smpcmentioning
confidence: 99%
“…Carbon fiber LASMPC materials are capable of near-infrared light with a maximal power density of 2W/cm 2 for actuation, and these carbon-based filler materials had demonstrated developed not only photothermal efficiency but also enhanced structural properties . The effects of rare earth organic compounds and glass fiber filler on the main matrix have been tested by Herath et al, and the various properties have been investigated. It has been found that the photothermal triggering capacity of the SMPC increased drastically with different weight percentages.…”
Section: Actuation Mechanism For Smpcmentioning
confidence: 99%
“…In addition to microwave-active shape-memory materials, photo/thermal-active shape-memory material is also one of the materials that facilitate remote driving (Herath et al, 2019;Huang et al, 2019;Li et al, 2019;Kang et al, 2019). Photo/thermal actuators are made by doping fillers in a photo/thermal-active shape-memory polymer matrix (Lu et al, 2014;Yi et al, 2014).…”
Section: Other Types Of Graphene/epoxy Compositesmentioning
confidence: 99%
“…The matrix binds these fillers and fibre reinforcements together and distributes induced stresses through the whole shape memory polymer composite (SMPC). Particulate fillers such as graphene oxide (GO) [8], multi walled carbon nanotubes (MWCNT) [9], carbon black (CB) [10] and rare earth organic fillers [11] produce thermal [8], electrical [9,10] and photothermal [11] property enhancements, and fibre reinforcements improve structural properties such as resistance to cyclic loading [12], modulus, stiffness and strength [5]. SMPC hinges [13], truss booms [14], solar arrays [13], reflector antennas [15,16], morphing structures [17,18] and mandrels [19] are a few of the renowned applications proposed for SMPCs.…”
Section: Introductionmentioning
confidence: 99%